A Hybrid Biofuel and Triboelectric Nanogenerator for Bioenergy Harvesting - Li, Hu; Zhang, Xiao; Zhao, Luming; Jiang, Dongjie; Xu, Lingling; Liu, Zhuo; Wu, Yuxiang; Hu, Kuan; Zhang, Ming‑Rong; Wang, Jiangxue; Fan, Yubo; Li, Zhou (Nano-Micro Letters, 2020)
Various types of energy exist everywhere around us, and these energies can be harvested from multiple sources to power micro-/nanoelectronic system and even personal electronic products. In this work, we proposed a hybrid energy-harvesting system (HEHS) for potential in vivo applications. The HEHS consisted of a triboelectric nanogenerator and a glucose fuel cell for simultaneously harvesting biomechanical energy and biochemical energy in simulated body fluid. These two energy-harvesting units can work individually as a single power source or work simultaneously as an integrated system. This design strengthened the flexibility of harvesting multiple energies and enhanced corresponding electric output. Compared with any individual device, the integrated HEHS outputs a superimposed current and has a faster charging rate. Using the harvested energy, HEHS can power a calculator or a green light-emitting diode pattern. Considering the widely existed biomechanical energy and glucose molecules in the body, the developed HEHS can be a promising candidate for building in vivo self-powered healthcare monitoring system. Highlights: 1 A triboelectric nanogenerator (TENG) and a glucose fuel cell (GFC) were separately designed to harvest biomechanical energy from body motion and biochemical energy from glucose molecules. 2 A hybrid energy-harvesting system (HEHS) which consisted of TENG and GFC was developed successfully, and it can simultaneously harvest biomechanical energy and biochemical energy.